DIABETIC RETINOPATHY: IMPORTANCE OF PRIMARY CARE PHYSCIAN IN SCREENING - Tamma, Naveen Kumar; Reddy, T Naga; Radha Kishan, N (Journal of Drug Delivery and Therapeutics, 2015)
Objective: TheÂ objective ofÂ Â this studyÂ isÂ importanceÂ ofÂ primary care physician in screeningÂ diabeticÂ retinopahyÂ Â patientsMaterial andÂ MethodsÂ : Patients ofÂ type-2Â diabetes mellitusÂ attendingÂ diabetic clinic in melakaÂ manipalÂ medical college , malaysia wereÂ prospectivelyÂ reviewed. Risk factors associatedÂ Â inÂ studyÂ population wereÂ assessedÂ byÂ biochemical parameters, clinical examinationÂ , retinal photographsÂ andÂ referredÂ toÂ ophthalmologyÂ clinic.Results: TheÂ prevalence ofÂ nonÂ proliferative andÂ proliferative diabetic retinopathyÂ withÂ type-2 diabeticÂ patientsÂ was 17%Â and 1%Â Â withÂ history of decreasedÂ in visionÂ above age group ofÂ 50 yearsÂ . In additionÂ theÂ riskÂ factorsÂ in theÂ study groupÂ associated withÂ theÂ developmentÂ of diabetic retinopathyÂ areÂ Â uncontrolledÂ HbA1cÂ levels (Â 27%) , high BMIÂ (38%Â ),Â increased total cholesterol (9% )Â , uncontrolled fasting blood sugar levels (47%),Â Â andÂ increasedÂ duration of diabetes. Conclusion: DiabeticÂ retinopahyÂ is highly prevalent in patients with type-2 diabetes mellitus. Our findingsÂ indicatesÂ primary care physiciansÂ areÂ Â well educatedÂ in regards to diabetic eye diseaseÂ andÂ in identificationÂ ofÂ risk factors dueÂ toÂ number ofÂ years experience. Keywords:Â Proliferative and non proliferative diabetic retinopathy, risk factors, visual disability, type -2 diabetes mellitus Â